User Authentication Using Grid Based Method - Noratiqah Md Ariffin, Siti; Fadzil Abdul Kadir, Mohd; Nazari Mohd Rose, Ahmad; Afendee Mohamed, Mohamad; Rasid Mamat, Abd (International Journal of Engineering and Technology, 2018)
Grid recognition authentication is a method of securing user logins. This project is based on user authentication in Smartphone using grid, images, and pattern. It is an innovation from the existing security lock that used in the Smartphone. A smartphone usually consists the authentication techniques such as draw a pattern or inserting a password. But nowadays, those techniques are not completely secure because it is very easy to break through different type of attack like brute force, dictionary attack or key logger. In this project, a tool based Grid Based Method will be developed which is important to increase the security of the smartphone that using an iOS platform. By using this tool, the codes are difficult to break because the grids are hidden behind the image. Users can identify the cells that were selected in a grid during the registration stage.Â